The Effect Of Profitability And Liquidity On Company Value Mediated By Dividend Policy In Property, Real Estate, And Building Construction Companies Listed On The Indonesia Stock Exchange (IDX) - Veronicha, Veronicha; Budidarma, I Gusti Agung Musa (Publikasi Indonesia, 2023)
The purpose of this study is to determine the effect of profitability, liquidity, and dividend policy on firm value. This study also aims to determine the indirect effect between profitability and liquidity on firm value through the dividend policy. This research used property, real estate, and building construction companies listed in Indonesia Stock Exchange. The research uses five recent years since 2018 until 2022 and selected by purposive sampling method. The analysis was performed using multiple linear regressions analysis method.